Dominance of benthic fluxes in the oceanic beryllium budget and implications for paleo-denudation records - Deng, Kai; Rickli, Jörg; Suhrhoff, Tim Jesper; Du, Jianghui; Scholz, Florian; Severmann, Silke; Yang, Shouye; McManus, James; Vance, Derek (Science Advances, 2023)
The ratio of atmosphere-derived 10Be to continent-derived 9Be in marine sediments has been used to probe the long-term relationship between continental denudation and climate. However, its application is complicated by uncertainty in 9Be transfer through the land-ocean interface. The riverine dissolved load alone is insufficient to close the marine 9Be budget, largely due to substantial removal of riverine 9Be to continental margin sediments. We focus on the ultimate fate of this latter Be. We present sediment pore-water Be profiles from diverse continental margin environments to quantify the diagenetic Be release to the ocean. Our results suggest that pore-water Be cycling is mainly controlled by particulate supply and Mn-Fe cycling, leading to higher benthic fluxes on shelves. Benthic fluxes may help close the 9Be budget and are at least comparable to, or higher (~2-fold) than, the riverine dissolved input. These observations demand a revised model framework, which considers the potentially dominant benthic source, to robustly interpret marine Be isotopic records.